Inhibition of swarming and virulence factor expression in Proteus mirabilis by resveratrol - Wang, Won-Bo; Lai, Hsin-Chih; Hsueh, Po-Ren; Chiou, Robin Y.-Y; Lin, Shwu-Bin; Liaw, Shwu-Jen (Journal of medical microbiology, 2006)
1 , 2 Graduate Institute of Microbiology 1 and Department and Graduate Institute of Clinical Laboratory Sciences and Medical Biotechnology 2 , College of Medicine, National Taiwan University, 10016 no. 1 Chang-Te Street, Taipei, Taiwan, Republic of China 3 Department of Laboratory Medicine, National Taiwan University Hospital, Taipei, Taiwan, Republic of China 4 Department of Food Science, National Chiayi University, Chiayi, Taiwan, Republic of China Correspondence Shwu-Jen Liaw s-jliawatha.mc.ntu.edu.tw Received 4 April 2006 Accepted 3 July 2006 Resveratrol (3,5,4-trihydroxy- trans -stilbene) is a phytoalexin compound with anti-inflammatory and antioxidant activities. The effect of resveratrol on swarming and virulence factor expression of Proteus mirabilis , an important pathogen infecting the urinary tract, was determined on swarming agar plates with and without the compound. Bacteria harvested at different times were assayed for cell length and the production of flagella, haemolysin and urease. Resveratrol inhibited P. mirabilis swarming and virulence factor expression in a dose-dependent manner. Resveratrol significantly inhibited swarming at 15 µg ml 1 , and completely inhibited swarming at 60 µg ml 1 . Inhibition of swarming and virulence factor expression was mediated through RsbA, a His-containing phosphotransmitter of the bacterial two-component signalling system possibly involved in quorum sensing. Complementation of an rsbA -defective mutant with the rsbA gene restored its responsiveness to resveratrol. The compound also inhibited the ability of P. mirabilis to invade human urothelial cells. These findings suggest that resveratrol has potential to be developed as an antimicrobial agent against P. mirabilis infection. Abbreviations: QS, quorum sensing; resveratrol, 3,5,4-trihydroxy- trans -stilbene; ROS, reactive oxygen species.